Navigating the Storm: Unraveling the Factors Shaping Adolescent Anxiety Amid the COVID-19 Pandemic - Rini Nur Diana; Mamnuah Mamnuah; Dwi Ernawati (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
The COVID-19 epidemic has significantly impacted adolescent mental health, particularly in cases of anxiety. The underlying causes, though, are yet unknown. The goal of this study is to identify any potential influences on adolescent anxiety during the COVID-19 epidemic. Cross-sectional time series analysis is the method used in this investigation. The 188 teenagers who made up the study's samples ranged in age from 15 to 18 years old. The sampling method made use of the probability sampling. The Generalized Anxiety Disorder-7 (GAD-7) questionnaire was used as the instrument for gathering the data. Then, univariate, bivariate, and multivariate were used in the statistical test. Most of the respondents, namely 143 respondents (76.1%) experienced anxiety. The most influential factor in anxiety is the source of information (p value 0.020). The factors related to anxiety were sources of information, resilience, loneliness, social support, and having positive COVID-19 patients within the family or around the family environment. During the COVID-19, the source of information variable was found to be the most important variable related to the anxiety. Lack of clear information makes thingking worse and increases adolescent anxiety. It is recommended for healthcare services and community health centers to provide accurate information about COVID-19 in educational institutions to reduce adolescent anxiety.